Method for manufacturing biaxially stretched laminated film
Patent Information
- Application Number
- JP2023139600
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0010】 本発明により、長手方向の周期的な厚みムラに起因する品質の変動を抑えることが可能な二軸配向積層フィルムの製造方法を提供することができる。
Smart Images

Figure 2025033694000004 
Figure 2025033694000001 
Figure 2025033694000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a biaxially oriented laminate film. [Background technology]
[0002] A method of laminating resins with different properties to give various optical properties to a film is known. A method of manufacturing such a laminated film is known in which a sheet of laminated resins with different properties is stretched in two directions, the length direction and the width direction, to produce a biaxially oriented laminated film while minimizing the amount of added particles, in order to give the film excellent transparency and the required optical properties. In addition to this, a method has recently been known in which atmospheric pressure glow discharge is performed on the surface of an unstretched sheet before crystallization progresses, and the sheet is stretched after the molecular chains on the sheet surface are destroyed, to create fine protrusions on the film surface that are not due to added particles.
[0003] Such laminated films require a high degree of uniformity in quality. However, it has become clear that laminated films that have been subjected to atmospheric pressure glow discharge treatment have periodic variations in quality depending on the subsequent processing.
[0004] In the case of unstretched sheets containing particles, the particles remain buried in the unstretched sheet during the preheating stage before stretching and do not appear on the surface, so even if there is a difference in the diameter or amount of added particles on the front and back sides, there is not much difference in the contact state with the roll on the front and back sides of the sheet. However, in the case of a sheet that has been subjected to atmospheric pressure glow discharge treatment on one side, the molecular chains on one side of the sheet are destroyed by the treatment, so there is a difference in the contact state with the roll on the front and back sides of the sheet even before stretching. Therefore, it has been found that periodic fluctuations occur in the quality of the final laminated film and that it also affects film formability.
[0005] In recent years, high smoothness and transparency are required for films used as support materials for dry film resists, and high smoothness is also required for films used for ceramic capacitors. For these reasons, film surface treatment using atmospheric pressure glow discharge treatment has been performed, and in fact, Patent Documents 1 and 2 disclose a method of performing atmospheric pressure glow discharge treatment on the smooth surface side. Patent Document 3 discloses a method of performing atmospheric pressure glow discharge treatment on the transport surface side to which a large amount of particles are added. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2022-52031 [Patent Document 2] Patent Publication No. 2022-52717 [Patent Document 3] JP 2021-109441 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the methods of Patent Documents 1 and 2, the processing speed must be slowed down for the glow discharge treatment, and when attempting to obtain a polyester film of a certain width or more, quality fluctuations due to periodic thickness unevenness in the longitudinal direction may occur. The same tendency was observed in the method of Patent Document 3. The present invention aims to solve the above problems and provide a method for producing a biaxially oriented laminate film that suppresses quality fluctuations due to periodic thickness unevenness in the longitudinal direction and is suitable for use as a dry film resist support or a film for a ceramic capacitor. [Means for solving the problem]
[0008] In order to solve the above problems, the present invention employs the following means: That is, a method for producing a biaxially oriented laminate film in which layers A, B and C are laminated in this order, where layers A and B are made of thermoplastic resin compositions A and B having different intrinsic viscosities (IV), respectively, and layer C is made of a thermoplastic resin composition C containing more particles than the thermoplastic resin compositions A and B, The method for producing a biaxially oriented laminate film includes, in this order, a discharge treatment step of subjecting the surface of the unstretched laminate sheet on the A-layer side to atmospheric pressure glow discharge treatment, a longitudinal stretching step of preheating and stretching in the longitudinal direction using rolls, a transverse stretching step of preheating and stretching in the width direction using a tenter device, and a winding step of winding up the film as an intermediate product, and satisfies all of the following 1) to 3). 1) When the IV of the thermoplastic resin composition A and the IV of the thermoplastic resin composition B are IV(A) and IV(B), respectively, the following formulae 1 and 2 are satisfied. Equation 1: 0.500< IV(A) <0.595 Equation 2: 0.030<(IV(B)-IV(A))<0.150 2) The content of the particles in the thermoplastic resin composition C is from 0.002% by mass to 1.000% by mass, and the volume average particle diameter of the particles is from 10 nm to 400 nm. 3) In the longitudinal stretching step, the stretching in the longitudinal direction is carried out by one section of inter-roll stretching, and the stretch ratio is 3.0 times or more.
[0009] The method for producing the biaxially oriented laminate film of the present invention can also be implemented in the following manner. (1) A method for producing a biaxially oriented laminate film in which layers A, B, and C are laminated in this order, where layers A and B are made of thermoplastic resin compositions A and B having different intrinsic viscosities (IV), respectively, and layer C is made of a thermoplastic resin composition C containing more particles than the thermoplastic resin compositions A and B, the method comprising the steps of: a discharge treatment step of subjecting the surface of an unstretched laminate sheet on the side of layer A to atmospheric pressure glow discharge treatment; a longitudinal stretching step of preheating and stretching in the longitudinal direction using a roll; a transverse stretching step of preheating and stretching in the width direction using a tenter device; and a winding step of winding up the film as an intermediate product, in this order, and wherein all of the following 1) to 3) are satisfied: 1) When the IV of the thermoplastic resin composition A and the IV of the thermoplastic resin composition B are IV(A) and IV(B), respectively, the following formulae 1 and 2 are satisfied. Equation 1: 0.500< IV(A) <0.595 Equation 2: 0.030<(IV(B)-IV(A))<0.150 2) The content of the particles in the thermoplastic resin composition C is from 0.002% by mass to 1.000% by mass, and the volume average particle diameter of the particles is from 10 nm to 400 nm. 3) In the longitudinal stretching step, the stretching in the longitudinal direction is carried out by one section of inter-roll stretching, and the stretch ratio is 3.0 times or more. (2) The method for producing a biaxially oriented laminate film according to (1), wherein the thickness of the layer A is 1.0 μm or more and 2.0 μm or less, and the thickness of the layer A accounts for less than 15% of the total thickness. (3) The method for producing a biaxially oriented laminate film according to (1) or (2), wherein the thickness of the C layer is 0.5 μm or more and 3.0 μm or less. (4) The method for producing a biaxially oriented laminate film according to any one of (1) to (3), wherein the biaxially oriented laminate film has a thickness of 15 μm or more and 39 μm or less. (5) The method for producing a biaxially oriented laminate film according to any one of (1) to (4), wherein the intermediate product has a width of 2000 mm or more. (6) The method for producing a biaxially oriented laminate film according to any one of (1) to (5), wherein the biaxially oriented laminate film is used for a dry film resist support or a ceramic capacitor. Effect of the Invention
[0010] According to the present invention, it is possible to provide a method for producing a biaxially oriented laminate film that is capable of suppressing quality fluctuations caused by periodic thickness unevenness in the longitudinal direction. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a schematic diagram for explaining thickness unevenness that appears periodically in the longitudinal direction of a film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The method for producing the biaxially oriented laminate film of the present invention will be specifically described below. The method for producing the biaxially oriented laminate film of the present invention is a method for producing a biaxially oriented laminate film in which layers A, B, and C are laminated in this order, where layers A and B are made of thermoplastic resin compositions A and B having different intrinsic viscosities (IV), and layers C are made of a thermoplastic resin composition C containing more particles than the thermoplastic resin compositions A and B, and the method comprises a discharge treatment step of subjecting the surface of the unstretched laminate sheet on the side of the layer A to atmospheric pressure glow discharge treatment, a longitudinal stretching step of preheating and stretching in the longitudinal direction using a roll, a transverse stretching step of preheating and stretching in the width direction using a tenter device, and a winding step of winding up the film as an intermediate product, in this order, and is characterized in that it satisfies all of the following 1) to 5). 1) When the IV of the thermoplastic resin composition A and the IV of the thermoplastic resin composition B are IV(A) and IV(B), respectively, the following formulae 1 and 2 are satisfied. Equation 1: 0.500< IV(A) <0.595 Equation 2: 0.030<(IV(B)-IV(A))<0.150 2) The content of the particles in the thermoplastic resin composition C is from 0.002% by mass to 1.000% by mass, and the volume average particle diameter of the particles is from 10 nm to 400 nm. 3) In the longitudinal stretching step, the stretching in the longitudinal direction is carried out by one section of inter-roll stretching, and the stretch ratio is 3.0 times or more.
[0013] In the method for producing a biaxially oriented laminate film of the present invention, biaxial orientation means that the molecules are oriented in two perpendicular directions, which is usually obtained by stretching an unstretched sheet in two perpendicular directions (for example, the longitudinal direction and the width direction). Here, the longitudinal direction refers to the direction in which the film (sheet) runs during the production process, and the width direction refers to the direction perpendicular to the longitudinal direction within the film plane.
[0014] In the manufacturing method of the biaxially oriented laminate film of the present invention, when the IV of the thermoplastic resin composition A and the IV of the thermoplastic resin composition B are IV(A) and IV(B), respectively, it is important that the following formulas 1 and 2 are satisfied. Equation 1: 0.500< IV(A) <0.595 Equation 2: 0.030<(IV(B)-IV(A))<0.150 Surface treatment using atmospheric pressure glow discharge treatment is more effective the lower the binding strength of the molecular chains of the thermoplastic resin being treated (the lower the intrinsic viscosity), but if a thermoplastic resin with too low an intrinsic viscosity is used, it will result in insufficient strength and dimensional precision in the final film, and also in reduced process stability in the film manufacturing process.For this reason, it is necessary to use a resin with a low intrinsic viscosity partially; specifically, it is used as thermoplastic resin A, which will be the smooth side of the film, and atmospheric pressure glow discharge treatment is performed on that side.
[0015] However, there are technical problems in forming a resin with a low intrinsic viscosity into a film, and it is particularly difficult to extrude it with a stable pressure in an extruder, so when forming it into a laminated film, it is difficult to laminate it thinly and uniformly. For this reason, the IV(A) needs to be more than 0.500. If the intrinsic viscosity is less than that, it is difficult to laminate it thinly and uniformly. If the lamination is not uniform, the atmospheric pressure glow discharge will not be applied uniformly, which will cause variations in film characteristics and lead to uneven thickness. In addition, the IV(A) that is advantageous for atmospheric pressure glow discharge treatment is less than 0.595. There is no difference in effect between thermoplastic resins with a value of 0.595 or more, so there is no need to laminate thermoplastic resin A on thermoplastic resin B. It is more preferable that IV(A) is 0.510 or more and 0.580 or less.
[0016] The same applies when the difference in intrinsic viscosity between thermoplastic resins A and B (IV(B)-IV(A)) is less than 0.030. However, if the difference in intrinsic viscosity (IV(B)-IV(A)) is 0.150 or more, layers A and B tend to peel off during the film formation process, leading to surface defects in the film, so it is preferable that the difference in intrinsic viscosity (IV(B)-IV(A)) is less than 0.150. It is more preferable that the difference in intrinsic viscosity (IV(B)-IV(A)) is 0.05 or more and 0.13 or less.
[0017] In the method for producing a biaxially oriented laminate film of the present invention, it is important that the content of particles in the thermoplastic resin composition C is 0.002% by mass or more and 1.000% by mass or less, and the volume average particle diameter of the particles is 10 nm or more and 400 nm or less. The surface obtained by the atmospheric pressure glow discharge treatment and the subsequent stretching and heat treatment has a very smooth surface, but because of its smoothness, in order to wind the molded film into a roll, it is necessary to contain particles in the C layer, which is the opposite surface, to maintain runnability and at the same time to prevent deformation of the film surface, such as the transfer of protrusions due to the particles in the C layer to the B layer when wound. For this purpose, the content and size of the particles in the thermoplastic resin composition C are preferably 0.002% by mass or more and 1.000% by mass or less, and the volume average particle diameter of the particles is 10 nm or more and 400 nm or less. More preferably, layer C simultaneously contains 0.010% by mass or more and 0.020% by mass or less of particles having a volume average particle diameter of 400 nm or more and 500 nm or less, and 0.055% by mass or more and 0.065% by mass or less of particles having a volume average particle diameter of 250 nm or more and 350 nm or less, so that the volume average particle diameter of the particles in layer C as a whole is 400 nm or less.
[0018] In the manufacturing method of the biaxially oriented laminate film of the present invention, it is important that the stretching in the longitudinal direction is performed by one section of inter-roll stretching, and the stretching ratio is 3.0 times or more. When a film is usually produced, a thermoplastic resin is discharged from a die and quenched on a roll to form a non-oriented film. After that, the non-oriented film is preheated in the longitudinal direction using multiple rolls and stretched. At this time, even if the size and number of particles contained on the front and back sides are different in the design, almost all of the particles are buried in the film and do not appear on the surface while it is non-oriented, so there is no significant difference in the surface morphology on the front and back. As the stretching progresses, the buried particles gradually emerge on the film surface, forming a process in which different surface morphologies are formed on the front and back. However, the non-oriented film that has been treated with atmospheric pressure glow discharge on one side has a difference in the surface structure and slipperiness on the front and back immediately after the treatment due to the destruction of the molecular chains by the treatment, and is more likely to cause adhesion and peeling between the rolls in the preheating and stretching process than the non-oriented film described above. For this reason, if the stretching section is set to two or more sections and stretching is performed stepwise, periodic thickness unevenness may occur when the section changes and the stretching ratio differs. For this reason, it is important that the stretching in the longitudinal direction is between rolls in one section. It is also important that the stretching ratio is 3.0 times or more. If the stretching ratio is less than that, the strength of the film is insufficient for use as a dry film resist support or a film for ceramic capacitors.
[0019] In the method for producing the biaxially oriented laminate film of the present invention, it is preferable that the width of the intermediate product is 2000 mm or more. As described above, the non-oriented film, one side of which has been subjected to atmospheric pressure glow discharge treatment, is prone to adhesion and peeling between the rolls in the preheating and stretching process, but the wider the width of the film to be formed, the greater the tendency for adhesion and peeling. However, if the width of the intermediate product usable as a product is less than 2000 mm, when it is used as a film for dry film resist support or ceramic capacitor, the productivity decreases in relation to the width of the final product. Since the method for producing the film of the present invention can suppress the occurrence of adhesion and peeling, it is easy to produce the intermediate product with a width of 2000 mm or more. The upper limit of the width of the intermediate product is not particularly limited, but it can be about 10,000 mm.
[0020] The film obtained by the method for producing a biaxially oriented laminate film of the present invention preferably has a thickness unevenness R of less than 0.35 μm in a length of 12 cm or less in the longitudinal direction with a periodicity of 2.0 m to 3.8 m. The thickness unevenness of the film leads to fluctuations in the film properties, and the more abrupt the thickness unevenness, the greater the fluctuation in the film properties. In particular, when a film is formed using multiple rolls, the greater the fluctuation in the adhesion / peeling state between the rolls used in the process and the film being formed, the greater the thickness unevenness may be. To use the film as a dry film resist support or a ceramic capacitor, it is preferable that the thickness unevenness R is 0.25 μm or more and less than 0.35 μm in a length of 12 cm or less in the longitudinal direction with a periodicity of 2.0 m to 3.8 m within a measurement length of 28 m in the longitudinal direction, and more preferably less than 0.25 μm.
[0021] In the method for producing a biaxially oriented laminate film of the present invention, it is preferable that the thickness of the A layer is 1.0 μm or more and 2.0 μm or less, and the thickness of the A layer accounts for less than 15% of the total thickness. When thermoplastic resin compositions with different IVs are laminated to form a film, if the difference in IV between the front and back of the film or between the front layer and the inner layer is large, the film may curl in a certain direction, which may deteriorate processability and usability. In order to avoid this phenomenon and to perform atmospheric pressure glow discharge treatment uniformly on the film surface to obtain uniform film characteristics, it is preferable that the thickness of the A layer is 1.0 μm or more and 2.0 μm or less, and the thickness of the A layer accounts for less than 15% of the total thickness, and more preferably, the thickness of the A layer is 1.0 μm or more and 2.0 μm or less, and the thickness of the A layer accounts for 3% or more and less than 12% of the total thickness.
[0022] In the method for producing a biaxially oriented laminate film of the present invention, the thickness of the C layer is preferably 0.5 μm or more and 3.0 μm or less. If the thickness of the C layer is thin relative to the volume average particle diameter of the particles contained in the thermoplastic resin composition C, the contained particles cannot be uniformly dispersed, and the dispersion and height of the protrusions made by the contained particles on the C layer surface may become non-uniform. In order to suppress this quality variation and reduce the total amount of contained particles to reduce production costs, it is preferable to make the thickness of the C layer 0.5 μm or more and 3.0 μm or less. A more preferable C layer thickness varies depending on the particle diameter of the contained particles in the thermoplastic resin composition C, but is preferably 0.5 μm or more and 3.0 μm or less, and at the same time, is preferably 1.2 times or more and 1.4 times or less of the volume average particle diameter of the largest particle contained in the thermoplastic resin composition C.
[0023] In the manufacturing method of the biaxially oriented laminate film of the present invention, when the film is used as a dry film resist support or a ceramic capacitor film, the final film thickness is preferably 15 μm or more and 39 μm or less in view of its processing characteristics and handling properties.
[0024] [Manufacturing method of biaxially oriented polyester film] Next, the method for producing the biaxially oriented polyester film of the present invention The method will be described with reference to examples, but the present invention is not to be construed as being limited to those obtained by such examples.
[0025] The polyester film used in the present invention can be obtained by a conventional polymerization method. For example, a dicarboxylic acid component such as terephthalic acid or its ester-forming derivative and a diol component such as ethylene glycol or its ester-forming derivative are transesterified or esterified by a known method, followed by melt polymerization. If necessary, the polyester obtained by the melt polymerization may be subjected to solid-phase polymerization at a temperature below the melting point of the polyester.
[0026] The polyester film of the present invention can be obtained by a conventionally known production method. Specifically, the polyester film of the present invention can be obtained by a method in which a raw material, which is dried as necessary, is heated and melted in an extruder, extruded from a die onto a cooled casting drum, and processed into a sheet (melt casting method).
[0027] When the biaxially oriented laminated polyester film of the present invention is manufactured by the melt casting method, a method (co-extrusion method) is preferably used in which an extruder is used for each layer constituting the biaxially oriented laminated polyester film, the raw materials of each layer are melted, and these are laminated in a molten state in a merging device provided between the extrusion device and the die, and then introduced to the die, and extruded from the die onto a casting drum to process into a sheet. The laminated sheet is adhered by static electricity on a casting drum cooled to a surface temperature of 20°C to 60°C and cooled and solidified to produce an unstretched film. By setting the surface temperature of the casting drum to 20°C or higher, the crystalline polyester portion on the surface of the unstretched film can be further increased, and the effect of forming fine protrusions after stretching by plasma surface treatment using atmospheric pressure glow discharge can be obtained. In addition, by setting the surface temperature of the casting drum to 60°C or lower, the adhesion of the unstretched film to the casting drum can be suppressed, and an unstretched film with little thickness unevenness in the film running direction can be obtained. A more preferable range of the surface temperature of the casting drum is 25°C to 55°C.
[0028] The unstretched film thus obtained is then subjected to a surface treatment such as a plasma surface treatment by atmospheric pressure glow discharge. The surface treatment may be performed immediately after the unstretched film is obtained or after the film is stretched in the running direction (hereinafter sometimes referred to as the longitudinal direction), but in the present invention, it is preferable to perform the surface treatment on the unstretched film from the viewpoint of further promoting the formation of protrusions by the treatment. The surface treatment may be performed on either the surface that was in contact with the casting drum (drum surface) or the surface that is not in contact with the casting drum (non-drum surface).
[0029] (Sequential biaxial stretching) Regarding the stretching conditions when the unstretched film is biaxially stretched, when the polyester film of the present invention is mainly composed of polyester, it is preferable that the unstretched film is guided to a roll group heated to 70°C or higher, stretched in the longitudinal direction (longitudinal direction, i.e., the direction of travel of the film), and cooled by a roll group set at a temperature of 20°C to 50°C. There is no particular restriction on the lower limit of the heating roll temperature in the longitudinal stretching as long as it does not impair the stretchability of the sheet, but it is preferable that the temperature exceeds the glass transition temperature of the polyester resin used. As mentioned above, it is important that the longitudinal stretching is a one-section inter-roll stretching, and that the stretching ratio at this time is 3.0 times or more. A more preferable range of the stretching ratio is 3.0 times or more and 4.0 times or less.
[0030] The obtained uniaxially stretched film is preferably guided into a tenter while both ends are held with clips, and stretched 3 to 5 times in the direction perpendicular to the longitudinal direction (width direction) in an atmosphere heated to a temperature of 70°C or more and 160°C or less. Thereafter, it is preferable to heat-treat the stretched film to stabilize the internal orientation structure. The heat history temperature of the film during heat treatment can be confirmed by the temperature of the minute endothermic peak (sometimes called Tmeta) that appears just below the melting point temperature measured by a differential scanning calorimeter (DSC) described later. When polyester (melting point 255°C) is the main component, the tenter device setting temperature is preferably set so that the maximum temperature in the tenter is 200°C or more and 250°C or less, and when other thermoplastic resins are the main component, it is preferable to set it to the resin melting point -55°C or less and the resin melting point -5°C or less. By setting the heat treatment temperature to 200°C or more, the orientation of the biaxially oriented polyester film can be relaxed while promoting crystal growth, resulting in a film with excellent mechanical properties. In addition, by setting the heat treatment temperature to 250°C or less, the occurrence of film breakage due to melting of the polyester film can be suppressed, and the film can be produced with good productivity. A more preferable range is 220°C or more and 235°C or less.
[0031] When the main component is polyester resin, the range of Tmeta, which represents the heat history temperature of the film during heat treatment, is preferably 190°C or more and 245°C or less for the reasons described above. A more preferable range is 210°C or more and 230°C or less.
[0032] Furthermore, in order to impart dimensional stability after the heat treatment, it is preferable to perform a relaxation treatment (relaxation treatment) at a temperature lower than that of the heat treatment in the range of 1% to 6%. By setting the relaxation treatment at 1% or more, the dimensional stability of the biaxially oriented polyester film when used in a high-temperature environment can be improved, and by setting it at 6% or less, it is possible to continue applying a moderate tension to the biaxially oriented polyester film and prevent the thickness unevenness from worsening. In addition, the temperature during the relaxation treatment (relaxation treatment) is preferably 150°C to 220°C. By setting the temperature during the relaxation treatment (relaxation treatment) at 150°C or more, it is possible to suppress heat shrinkage during pressure bonding with a high-temperature roll in the lamination process, and the occurrence of wrinkles during lamination can be suppressed, and by setting it at 220°C or less, excessive crystallization of the film can be suppressed, and film breakage can be suppressed in the lamination process in which tension is applied and transported and processed.
[0033] The stretching ratio is from 3 to 5 times in both the longitudinal and transverse directions, and the area ratio (stretching ratio in the longitudinal direction × stretching ratio in the transverse direction) is preferably from 9 to 22 times, more preferably from 9 to 20 times. By setting the area ratio at 9 times or more, the molecular orientation of the obtained biaxially oriented polyester film can be promoted and the durability can be improved, and by setting the area ratio at 22 times or less, the occurrence of breakage during stretching can be suppressed.
[0034] In the manufacturing method of the biaxially oriented laminate film of the present invention, atmospheric pressure glow discharge treatment is performed on the surface of film A layer in the unstretched stage. However, in order to perform the required amount of treatment for a film used as a dry film resist support or a ceramic capacitor, it is usually necessary to have a long unstretched section in the manufacturing process and to utilize this section for treatment, or to reduce the processing speed if the unstretched section available for treatment is short.
[0035] In the manufacturing method of the biaxially oriented laminate film of the present invention, by using a thermoplastic resin composition with low molecular chain bonding strength (low intrinsic viscosity) for the treated surface, layer A, it is possible to achieve the required processing amount without reducing the processing speed even if the unstretched section is short. However, since a thermoplastic resin composition with a low intrinsic viscosity also has a low melt viscosity, it is difficult to extrude stably with a single-screw extruder during melt extrusion. For this reason, it is important to use a twin-screw kneading extruder that can arbitrarily control the discharge rate and screw rotation speed as the extruder used for layer A.
[0036] This is the proportion of the thermoplastic resin composition with low molecular chain binding strength (low intrinsic viscosity) in the entire film, but if the thickness of layer A is made extremely thick, the difference in properties between the front and back of the film will become large, and the film may curl up. Also, if it is used in layers B and C to increase the proportion of the entire film, the strength of the film will be insufficient and the formability of the film edge will deteriorate, leading to a decrease in film formability.
[0037] The thickness of the film after processing of the A layer is preferably 1.0 μm or more in order to obtain a uniform surface state by atmospheric pressure glow discharge treatment, but at the same time, it is preferably less than 15% of the total film thickness to prevent film curling. Furthermore, it is preferably 2.0 μm or less in order to obtain the film formation stability required for production. If it exceeds 2.0 μm, the formability of the film formation edge held by the tenter clip is unstable, and there are cases where the clip comes off.
[0038] In addition, when the unstretched film after the glow discharge treatment is preheated and stretched in the longitudinal direction using rolls, the difference in surface condition between the treated surface of layer A, where the molecular difference is being destroyed, and the surface of layer C, which is the opposite surface, causes adhesion and peeling between the preheating and stretching roll surfaces where the two surfaces are in contact. When the width of the film to be produced is narrow, this phenomenon is suppressed by the film edge, but the tendency becomes greater as the width of the film increases, and when the width of the film exceeds 1500 mm, the final film appears as a steep thickness unevenness defect at the preheating and stretching roll pitch period. In this case, for thickness unevenness with a longitudinal period of 2.0 m to 3.8 m, if the thickness unevenness R exceeds 0.35 μm in a length of 12 cm or less in the longitudinal direction, it is not preferable because it cannot be processed normally when used as a dry film resist support or a film for a ceramic capacitor.
[0039] For this reason, it is important to use an individual drive control method that can control the roll speed for each 1R / L in the process of preheating and longitudinal stretching, and to alleviate the state of adhesion and peeling. It is also possible to alleviate this state by using an induction heating roll to individually control the temperature of rolls that tend to stick and rolls that tend to peel, for each 1R / L.
[0040] For longitudinal stretching, whether individual drive control or induction heating rolls are used, it is necessary to adopt a stretching method that minimizes the contact area between the film and the roll during stretching in order to prevent adhesion and peeling. Stretching is performed longitudinally using the difference in peripheral speed between a pair of stretching rolls in one section, and a stretch ratio of 3.0 times or more is required to obtain the necessary strength for the film used as a dry film resist support or for ceramic capacitor applications.
[0041] The method for producing a biaxially oriented laminate film of the present invention includes, in this order, a preheating step in which an unstretched sheet is heated by contacting it with a plurality of rolls, and a longitudinal stretching step in which both sides of the unstretched sheet are heated by a radiation heater and the unstretched sheet is stretched in the longitudinal direction by the difference in peripheral speed between a pair of stretching rolls. The unstretched sheet refers to a sheet obtained by forming a molten thermoplastic resin into a sheet shape and cooling and solidifying it, and more specifically, refers to a sheet from when it is cooled and solidified by a casting drum until it passes through a downstream stretching roll. The pair of stretching rolls refers to two stretching rolls with different rotation speeds, and in a pair of stretching rolls, the downstream stretching roll usually has a higher rotation speed than the upstream stretching roll. The longitudinal direction refers to the direction in which the unstretched sheet (or film) runs during the production process, and the direction perpendicular to the longitudinal direction within the plane of the unstretched sheet or film is the width direction. The preheating step serves to raise the temperature of the unstretched sheet to a temperature at which it can be stretched, and the longitudinal stretching step serves to stretch the unstretched sheet in the machine direction to form a uniaxially oriented film oriented in that direction.
[0042] In atmospheric pressure glow discharge treatment, the film to be treated is introduced between opposing electrodes and an earth roll, a plasma-excitable gas is introduced into the device, and a high-frequency voltage is applied between the electrodes to excite the gas into plasma and generate a glow discharge between the electrodes, which causes the film surface to be finely ashed and forms protrusions.
[0043] The plasma-excitable gas refers to a gas that can be plasma-excited under the above-mentioned conditions.
[0044] Examples of the plasma exciting gas include rare gases such as argon, helium, neon, krypton, and xenon, nitrogen, carbon dioxide, oxygen, and fluorocarbons such as tetrafluoromethane, and mixtures thereof. The plasma exciting gas may be used alone or in combination of two or more types in any mixing ratio. From the viewpoint of running costs and discharge stability, it is preferable to use an exciting gas containing 90% or more nitrogen, and from the viewpoint of promoting ashing of the film surface and controlling the shape of protrusions on the surface, it is more preferable to use a mixed gas of nitrogen and oxygen. The frequency of the high-frequency voltage in the plasma treatment used is preferably in the range of 1 kHz to 100 kHz. The discharge treatment intensity (E value) obtained by the following method is 170 to 500 W·min / m for the thickness of a film mainly composed of polyester for use as a dry film resist support or a ceramic capacitor in the present application. 2 From the viewpoint of protrusion formation, it is preferable to perform the treatment at a temperature in the range of 180 to 390 W·min / m 2 If the discharge treatment strength (E value) is too low, the protrusions may not be formed sufficiently, and if the discharge treatment strength (E value) is too high, the thermoplastic resin film may be damaged.
[0045] <How to determine discharge treatment strength (E value)> E = Vp × Ip / (S × Wt) E: E value (W min / m 2 ) Vp: Applied voltage (V) Ip: Applied current (A) S: Processing speed (m / min) Wt: Processing width (m).
[0046] When the thermoplastic resin film of the present invention is produced by carrying out surface treatment such as the above-mentioned UV irradiation, corona treatment by arc discharge, or plasma treatment by glow discharge, the surface temperature of the film during the surface treatment is preferably 150°C or less. More preferably, it is 100°C or less. If the surface temperature is higher than 150°C, crystallization of the film progresses, and coarse protrusions may be formed on the surface, or the mobility of molecular chains in the film may increase, causing damage to the film by the surface treatment. The surface treatment temperature can be adjusted by cooling the surface opposite to the treatment surface with a cooling roll or the like.
[0047] [Measurement method] Intrinsic Viscosity (IV) of Thermoplastic Resins A measurement sample (thermoplastic resin or thermoplastic resin composition) was dissolved in 100 ml of orthochlorophenol (solution concentration C (measurement sample weight / solution volume) = 1.2 g / 100 ml), and the viscosity of the solution at 25°C was measured using an Ostwald viscometer. Similarly, the viscosity of the solvent was measured. Using the obtained solution viscosity and solvent viscosity, [η] was calculated according to the following formula, and the obtained value was regarded as the intrinsic viscosity (IV) of the entire polyester film. ηsp / C=[η]+K[η] 2 C (Here, ηsp = (solution viscosity / solvent viscosity)-1, and K is the Huggins constant (assumed to be 0.343).) When the solution in which the measurement sample was dissolved contained insoluble matters such as inorganic particles, the measurement was carried out using the following method. (1-1) Dissolve the measurement sample in 100 mL of orthochlorophenol to prepare a solution with a concentration of more than 1.2 g / 100 mL. The weight of the measurement sample provided in orthochlorophenol is the measurement sample weight. (1-2) Next, the solution containing the insoluble matter is filtered, and the weight of the insoluble matter and the volume of the filtrate after filtration are measured. (1-3) Add orthochlorophenol to the filtrate after filtration to adjust the ratio (weight of measured sample (g) - weight of insoluble matter (g)) / (volume of filtrate after filtration (mL) + volume of added orthochlorophenol (mL)) to 1.2 g / 100 mL. (For example, when a concentrated solution with a measurement sample weight of 2.0 g / solution volume of 100 mL is prepared, if the weight of the insoluble matter when the solution is filtered is 0.2 g and the volume of the filtrate after filtration is 99 mL, an adjustment is made by adding 51 mL of orthochlorophenol. ((2.0 g-0.2 g) / (99 mL+51 mL)=1.2 g / 100 mL)) (1-4) Using the solution obtained in (1-3), measure the viscosity at 25°C using an Ostwald viscometer, and use the obtained solution viscosity and solvent viscosity to calculate [η] according to the above formula, and the obtained value is the intrinsic viscosity (IV).
[0048] [Volume average particle size of C layer particles] The polymer was removed from the C layer by plasma low-temperature ashing to expose the particles. The treatment conditions were selected so that the polymer was ashed but the particles were not damaged as much as possible. The treated sample was observed with a scanning electron microscope (SEM; Hitachi, Ltd., S-4000 type), and the particle image was imported into an image analyzer (Nireco Corporation, LUZEX_AP), and the equivalent circle diameter was measured to determine the volume average particle diameter of the particles. The magnification of the SEM was appropriately selected from 5000 to 20000 times depending on the particle diameter. The observation points were arbitrarily changed, and the equivalent circle diameter of at least 400 particles was measured to determine the volume average particle diameter. When measuring the volume average particle diameter of the particles, if no particles were observed even after checking 10 fields of view at 5000 times when observing with SEM and TEM, it was determined that the particles were not substantially contained.
[0049] [C layer particle content] 1 g of the sample, which was obtained by scraping off only the C layer, was placed in 200 ml of 1N-KOH methanol solution and heated to reflux to dissolve the polymer. 200 ml of water was added to the solution after dissolution was completed, and the liquid was then centrifuged to settle the particles, and the supernatant was removed. The particles were washed with more water, and the centrifugation was repeated twice. The particles thus obtained were dried, and their mass (g) was measured to calculate the particle concentration (mass%) contained in the P1 layer of the biaxially oriented polyester film. When the contained particles contained organic particles, a solvent that dissolves the polymer but not the organic particles was selected, the polymer was dissolved without heating under reflux, and the particles were centrifuged to calculate the particle content (mass%) in layer C. Whether the contained particles are organic or inorganic can be confirmed by the presence or absence of detection of inorganic matter when observing the particles using commonly known methods such as SEM-EDX.
[0050] [Total film thickness] The total thickness of the biaxially oriented polyester film was measured using a dial gauge at 30 random locations in the width direction of the film with 10 films stacked together in accordance with JIS K7130 (1992) A-2 method. The average value was divided by 10 to obtain the film thickness.
[0051] [Thickness of each film layer (thickness of layer A, thickness of layer C)] A cross section of the biaxially oriented polyester film is cut out in a direction parallel to the film width direction with a microtome. The cross section is observed with a scanning electron microscope at a magnification of 5000 to 20000 times to determine the thickness ratio of each laminated layer. The thicknesses of layers A and C are calculated from the determined lamination ratio and the film thickness obtained in the [Total Film Thickness] above.
[0052] [Film width (intermediate product width)] The film to be measured was spread out on a table, and the length in the width direction was measured with a metal ruler (JIS Class 1) to determine the total width of the film. In this case, the width direction is the direction perpendicular to the film production direction (longitudinal direction).
[0053] [Thickness Unevenness] Using Anritsu Corporation's film thickness tester "KG601A" and electronic micrometer "K306C," the thickness of a polyester film sampled at 30 m in length and 30 mm in width in the longitudinal direction of the polyester film was continuously measured at a conveying speed of 3 m / min, and a chart was output to a recorder. From the chart, thickness unevenness with a period of 2.0 m to 3.8 m in the longitudinal direction of the film was counted, with thickness unevenness R of 0.25 μm or more in a length of 12 cm or less in the longitudinal direction (hereinafter referred to as periodic thickness unevenness). [See Selection Figure 1] ◎: No periodic thickness irregularity with R of 0.25 μm or more exists within a measurement length of 28 m ○: Periodic thickness unevenness with R of 0.25 μm or more and less than 0.35 μm within a measurement length of 28 m There is one ×: Two or more periodic thickness irregularities with R of 0.25 μm or more exist within a measurement length of 28 m.
[0054] [Surface characteristics] [A layer surface properties] To count the number of protrusions on the surface of layer A, a sample of 50 mm square was taken and measured using a non-contact optical roughness measuring device (Zygo New View 7300) with a 50x objective lens over a measurement area of 139 μm × 104 μm (0.0145 mm 2), the position was changed randomly within a 50 mm square, and 80 visual fields (n=80) were measured. The sample was set on the stage so that the measurement Y axis was in the MD direction of the sample film, and the measurement was performed. For the obtained measurement data, the surface analysis software MetroPro built into the roughness meter was used to set the cutoff values of High Filter Wavelen to 1.65 μm and Low Filter Wavelen to 50.00 μm, and the number of protrusions exceeding 50 nm in height, Peaks (50 nm), was determined as the number of protrusions exceeding 50 nm in height when the Reference Band (bandwidth) was specified to 100 nm, and the number of protrusions exceeding 20 nm in height, Peaks (20 nm), was determined as the number of protrusions exceeding 20 nm in height when the Reference Band (bandwidth) was specified to 40 nm. The number of protrusions Xi (i=1 to 80) (pieces / mm 2 ) was calculated, and the average value of 80 fields of view was taken as the number of protrusions A. Xi(i=1~80)=(Peaks(20nm)-Peaks(50nm)) / Measurement area 0.0145mm 2 A = (X1 + X2 + X3 + ... + X80) / 80) The sample specimens were taken at the center and both ends of the overall width of the film, and the number of protrusions A at the center and both ends and the average number of protrusions A at the center and both ends were taken as Aave. The fluctuation rate (Amax-Amin) / Aave x 100 (%) was calculated from the maximum value Amax and minimum value Amin of the number of protrusions A at the center and both ends and evaluated according to the following criteria.
[0055] ◎: Average number of protrusions across the entire width of the film is 120 / mm 2 End And the fluctuation rate of the number of protrusions is less than 15%. ○: The average number of protrusions across the entire width of the film is 120 / mm 2 End And the fluctuation rate of the number of protrusions is 15% or more and less than 25%. △: Average number of protrusions across the entire width of the film is 120 or more And the fluctuation rate of the number of protrusions is 25% or more and less than 30%. ×: The average number of protrusions across the entire width of the film is less than 120. Alternatively, the fluctuation rate of the number of protrusions is 30% or more.
[0056] [C layer surface properties] The three-dimensional surface roughness (SRa) and ten-point average surface roughness (SRz) of the C layer surface were measured using a three-dimensional micro shape measuring instrument (model ET-350K) and a three-dimensional surface roughness analysis system (model TDA-22) manufactured by Kosaka Laboratory Co., Ltd. The conditions were as follows, and the average value of five measurements was used as the evaluation value, and evaluation was performed according to the following criteria. Stylus diameter: 2μm Stylus load: 0.04mN Longitudinal magnification: 50,000 times Cutoff: 0.08mm Feed pitch: 5μm Measurement length: 0.5mm Measurement area: 0.2mm 2 Measurement speed: 0.1mm / sec ○: SRa is less than 5 nm and SRz is less than 160 nm ×: SRa is 5 nm or more or SRz is 160 nm or more.
[0057] [Film strength] The sum of the Young's modulus in the longitudinal direction and the width direction of the film was defined as the film strength, and the Young's modulus was evaluated according to the following criteria.
[0058] The Young's modulus was measured in accordance with JIS-K7161 (1994). The measurement was performed using an Instron type tensile tester under the following conditions. The average value of five measurement results was taken as the Young's modulus in the present invention. Sample size: width 10mm x length 100mm Tensile strength: 200mm / min Measurement environment: temperature 23℃, humidity 65%RH Number of measurements: 5 measurements, calculated from the average value ◎: The sum of Young's moduli is 9.8 GPa or more ○: The sum of Young's moduli is 9.5 GPa or more and less than 9.8 GPa ×: The sum of Young's moduli is less than 9.5 GPa.
[0059] [Film curl] A strip measuring 50 mm in width and 300 mm in length was cut out, heated at 110°C for 30 minutes, and then stored for 10 minutes under the following conditions: The strip was held vertically with the length direction vertical and without tension, and the distance between the line connecting both ends of the 50 mm width and a line passing through the center of the strip (25 mm from both ends) and parallel to the above line was evaluated as film curl. Storage / Environmental measurement: Temperature 23℃, humidity 65%RH Number of measurements: 5 measurements were taken and the average value was calculated. Evaluation was based on the following criteria.
[0060] ○: Curl is 0.0 mm or more and 0.5 mm or less ×: Curl is greater than 0.5 mm.
[0061] [A layer extrusion controllability] When film formation was carried out under the conditions of the examples and comparative examples, the pressure at the gear pump outlet of layer A was continuously measured, and the ratio of the difference between the actually measured pressure and the set pressure was taken as extrusion controllability and evaluated according to the following criteria. Gear pump control method: Gear pump output pressure control Continuous measurement time: 6 hours Extrusion controllability: (set pressure - actual pressure) / set pressure = extrusion controllability ◎: Extrusion controllability is less than ±1.5% ○: All extrusion controllability is within the range of ±1.5% to less than ±2.5% △: The extrusion controllability is all within the range of ±2.5% or more and less than ±4.0%.
[0062] [Film forming property] When film formation was carried out under the conditions of the examples and comparative examples, the process tension applied to the clip drive motor of the tenter was continuously measured, and the ratio of the average value to the fluctuation range was taken as film formability and evaluated according to the following criteria. Vertical extension / clip motor control method: Draw control (motor speed ratio control) Continuous measurement time: 20 minutes Fluctuation: Maximum process tension - minimum process tension Film-forming ability: 1-(fluctuation range / average process tension value)=film-forming ability ◎: Film-forming property is 0.90 or more ○: Film-forming property is 0.87 or more and less than 0.90 △: Film-forming property is 0.84 or more and less than 0.87 ×: Film-forming property is less than 0.84.
[0063] [Preparation of Thermoplastic Resins 1, 2, 3, and 4] Terephthalic acid and ethylene glycol were polymerized in a conventional manner using antimony trioxide and magnesium acetate as catalysts, and four types of polyethylene terephthalate pellets with different intrinsic viscosities and essentially no particles were obtained by adjusting the amount of catalyst and reaction time. The intrinsic viscosities were 0.500 dl / g (thermoplastic resin-1), 0.626 dl / g (thermoplastic resin-2), 0.650 dl / g (thermoplastic resin-3), and 0.600 dl / g (thermoplastic resin-4), respectively.
[0064] [Preparation of Thermoplastic Resin-5] Separately, a water slurry of divinylbenzene / styrene copolymer crosslinked particles (volume average particle diameter 300 nm) obtained by a monomer adsorption method was added to the above thermoplastic resin-3 using a vented twin-screw kneader so that the amount added to the polyethylene terephthalate was 0.2% by weight, thereby obtaining polyethylene terephthalate pellets containing divinylbenzene / styrene copolymer crosslinked particles. The intrinsic viscosity of the obtained polyethylene terephthalate pellets was 0.650 dl / g.
[0065] [Preparation of Thermoplastic Resin-6] Thermoplastic resin-6 was prepared in the same manner as in the preparation of thermoplastic resin-5, except that the amount of divinylbenzene / styrene copolymer crosslinked particles was 2.0% by weight and the resin to be contained was thermoplastic resin-4. The intrinsic viscosity of the obtained polyethylene terephthalate pellets was 0.600 dl / g.
[0066] [Preparation of Thermoplastic Resin-7] Thermoplastic resin-7 was prepared in the same manner as in the preparation of thermoplastic resin-6, except that the volume average particle diameter of the divinylbenzene / styrene copolymer crosslinked particles was 450 nm and the amount added was 1.0 wt %. The intrinsic viscosity of the obtained polyethylene terephthalate pellets was 0.600 dl / g.
[0067] [Preparation of Thermoplastic Resin-8] In producing polyester in the same manner as in thermoplastic resin-1, 2, 3, and 4, calcium carbonate particles (volume average particle diameter 1100 nm) dispersed in ethylene glycol were added in an amount of 1.0% by weight relative to polyethylene terephthalate to obtain polyethylene terephthalate pellets containing calcium carbonate particles. The intrinsic viscosity of the resulting polyethylene terephthalate pellets was 0.614 dl / g.
[0068] [Thermoplastic resin composition] [Preparation of thermoplastic resin compositions a to h] Thermoplastic resin compositions a to h were prepared by uniformly mixing thermoplastic resins-1, 2, 3, 5, 6, 7, and 8 in the ratios shown in Table 1. The intrinsic viscosity of the thermoplastic resin composition in each of the A, B, and C layers of this composition was determined by sampling the polymer when melt-extruded in each extruder for each of the A, B, and C layers for each of the compositions a to h, and measuring the value obtained as above, and this was used as the intrinsic viscosity of the thermoplastic resin composition in each layer.
[0069] [Example 1] The compositions shown in Table 2 for each layer were fed to the extruders for layers A, B, and C. The mixture was melt extruded at 275°C and then extruded under constant pressure control by the respective gear pumps. After filtering, the mixture was laminated in a 3-layer junction block to form layers A, C, and B, and then passed through a slit die maintained at 285°C, wound around a casting drum, and cooled and solidified to obtain an unstretched sheet. At this time, the surface temperature of the casting drum was set to 25°C, and the charge density Q was set to 2mC / m 2The temperature of the unstretched sheet immediately after peeling from the cast drum was 25°C to 30°C.
[0070] The unstretched sheet was introduced between the opposing electrodes and the earth roll, nitrogen gas was introduced into the device, and the treatment intensity (E value) was 291 W·min / m 2 The surface of the layer A was subjected to atmospheric pressure glow discharge treatment under the following conditions:
[0071] The unstretched sheet after atmospheric pressure glow discharge treatment was preheated with a heating roll at 70 to 130 ° C, then stretched 3.3 times in the longitudinal direction at 110 to 120 ° C with the difference in peripheral speed between a pair of stretching rolls, and the uniaxially stretched film was cooled at 20 to 50 ° C. Furthermore, it was stretched 4.5 times in the width direction under hot air at 110 to 115 ° C in a stenter, and then heat-treated at 230 ° C for 5 seconds under a constant tension, and then subjected to a 3.2% relaxation treatment in the width direction to obtain an intermediate product of a biaxially oriented polyester film with a thickness of 16 μm and a film width of 2200 mm. The evaluation results of the obtained intermediate product are shown in Table 2.
[0072] [Examples 2, 3, and 4] An intermediate biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the thermoplastic resin compositions for layers A, B, and C were as shown in Table 2.
[0073] [Example 5] The thermoplastic resin compositions of layers A, B, and C were as shown in Table 2, and the thicknesses of layers A and B were adjusted so that layer A was 1.2 μm thick and the total thickness was 16 μm. An intermediate biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the thicknesses of layers A and B were adjusted so that layer A was 1.2 μm thick and the total thickness was 16 μm.
[0074] [Example 6] The thermoplastic resin compositions of layers A, B, and C are as shown in Table 2. The treatment intensity (E value) of the atmospheric pressure glow discharge treatment is 388 W min / m 2 An intermediate biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the above-mentioned steps were repeated.
[0075] [Example 7] The thermoplastic resin compositions of layers A, B, and C were as shown in Table 2, and the thicknesses of layers A and B were adjusted so that layer A was 1.2 μm thick and the total thickness was 38 μm. An intermediate biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the thicknesses of layers A and B were adjusted so that layer A was 1.2 μm thick and the total thickness was 38 μm.
[0076] [Example 8] An intermediate biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the thermoplastic resin compositions of layers A, B, and C were as shown in Table 2, the thickness of layer A was 1.5 μm, and the film width was 4600 mm.
[0077] [Example 9] The thermoplastic resin composition of layers A, B, and C is as shown in Table 2. The thickness of layers A and B is adjusted so that the thickness of layer A is 1.5μ and the total thickness is 16μ. The film width is 4600mm. The treatment intensity (E value) of the atmospheric pressure glow discharge treatment is 185W·min / m 2 An intermediate biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the above-mentioned steps were repeated.
[0078] [Example 10] The thermoplastic resin composition of layers A, B, and C is as shown in Table 2. The thickness of layers B and C is adjusted so that the thickness of layer C is 2.8μ and the total thickness is 31μ. The treatment intensity (E value) of the atmospheric pressure glow discharge treatment is 375W·min / m 2 An intermediate biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the above-mentioned steps were repeated. [Example 11] The thermoplastic resin compositions of layers A, B, and C are as shown in Table 2. The treatment intensity (E value) of the atmospheric pressure glow discharge treatment is 388 W min / m 2 An intermediate biaxially oriented polyester film was obtained in the same manner as in Example 9, except that the above-mentioned procedure was repeated.
[0079] [Comparative Examples 1 and 2] An intermediate biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the thermoplastic resin compositions for layers A, B, and C were as shown in Table 3.
[0080] [Comparative Example 3] The thermoplastic resin compositions of layers A, B, and C are as shown in Table 3. The treatment intensity (E value) of the atmospheric pressure glow discharge treatment is 388 W min / m 2 An intermediate biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the above-mentioned steps were repeated.
[0081] [Comparative Example 4] The thermoplastic resin composition of layers A, B, and C is as shown in Table 3. The thicknesses of layers A, B, and C are adjusted so that the thickness of layer A is 6.0 μm, the thickness of layer C is 2.8 μm, and the total thickness is 38 μm. The treatment intensity (E value) of the atmospheric pressure glow discharge treatment is 375 W·min / m 2 An intermediate biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the above-mentioned steps were repeated.
[0082] [Comparative Example 5] An intermediate biaxially oriented polyester film was obtained in the same manner as in Example 3, except that the longitudinal stretching was performed three times using three pairs of stretching rolls with different peripheral speeds to stretch the film by a total of 4.0 times.
[0083] [Comparative Example 6] An intermediate biaxially oriented polyester film was obtained in the same manner as in Comparative Example 5, except that the thermoplastic resin compositions of layers A, B, and C were as shown in Table 3.
[0084] [Table 1]
[0085] [Table 2]
[0086] [Table 3]
Claims
1. A method for producing a biaxially oriented laminate film, in which layers A, B and C are laminated in this order, where layers A and B are made of thermoplastic resin compositions A and B having different intrinsic viscosities (IV), respectively, and layer C is made of a thermoplastic resin composition C containing more particles than the thermoplastic resin compositions A and B, A method for producing a biaxially oriented laminate film, comprising the steps of: a discharge treatment step of subjecting the surface of the A-layer side of an unstretched laminate sheet to atmospheric pressure glow discharge treatment; a longitudinal stretching step of preheating and stretching in the longitudinal direction using rolls; a transverse stretching step of preheating and stretching in the width direction using a tenter device; and a winding step of winding up the film as an intermediate product, in this order; and satisfying all of the following 1) to 3). 1) When the IV of the thermoplastic resin composition A and the IV of the thermoplastic resin composition B are IV(A) and IV(B), respectively, the following formulae 1 and 2 are satisfied. Equation 1: 0.500< IV(A) < 0.595 Formula 2: 0.030<(IV(B)-IV(A))<0.150 2) The content of particles in the thermoplastic resin composition C is 0.002% by mass or more and 1.000% by mass or less, and the volume average particle diameter of the particles is 10 nm or more and 400 nm or less. 3) In the longitudinal stretching step, stretching in the longitudinal direction is carried out by one section of inter-roll stretching, and the stretch ratio is 3.0 times or more.
2. The method for producing a biaxially oriented laminate film according to claim 1 , wherein the thickness of the A layer is 1.0 μm or more and 2.0 μm or less, and the thickness of the A layer accounts for less than 15% of the total thickness.
3. The method for producing a biaxially oriented laminate film according to claim 1 or 2, wherein the thickness of the C layer is 0.5 μm or more and 3.0 μm or less.
4. The method for producing a biaxially oriented laminate film according to claim 1 or 2, wherein the thickness of the biaxially oriented laminate film is 15 μm or more and 39 μm or less.
5. The method for producing a biaxially oriented laminate film according to claim 1 or 2, wherein the intermediate product has a width of 2000 mm or more.
6. The method for producing a biaxially oriented laminate film according to claim 1 or 2, wherein the biaxially oriented laminate film is used for a dry film resist support or a ceramic capacitor.
Citation Information
Patent Citations
Polyester film
JP2021109441A
Biaxially oriented polyester film
JP2022052031A
Biaxially oriented laminated polyester film, release film and method for manufacturing biaxially oriented laminated polyester film
JP2022052717A